The Undergraduate College Education in USA: Schools with Best and Worst ROI - KOhli, Raj K (Archives of Business Research, 2016)
This study examined the ROI, total 4-year education cost, graduation rate and average loan amount for undergraduate education across schools in USA.  The results indicate that students from Southwest region of USA enjoyed highest mean ROI (6.69%) along with highest median ROI (6.50%) with minimum standard deviation of 2.03% among all five regional analyzed over 20-yeasr period.  Yale University reports the highest graduation rate of 98 percent in the nation.  Georgia Institute of Technology (In-state) enjoyed highest ROI of 12.30 percent over 20-years period of study